IMPLEMENTASI PEMBELAJARAN BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENUMBUHKAN KEAKTIFAN PESERTA DIDIK KELAS V DI MADRASAH IBTIDAIYAH - Khoiru Mutiya; Murtono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Active learning is an important aspect of learning. However, IPAS learning at Madrasah Ibtidaiyah still shows low student involvement, especially when the material is not associated with real experiences. The research aims to describe the application of the Contextual Teaching and Learning (CTL) approach to foster the activeness of class V students. The results of the study showed that the application of CTL through environmental observation, group discussions, and simple investigations was able to increase the courage to ask questions, involvement in discussions, and students' ability to relate the material to real situations. Learning is also in line with the seven components of CTL including constructivism, questioning, discovery, learning community, modeling, reflection, and authentic assessment so that the learning process becomes more meaningful. Strengthening teacher competence and adjusting the implementation of CTL to the characteristics of students at Madrasah Ibtidaiyah is recommended for optimizing its implementation.